Effect of cephalometric variables in paediatric snorers - Swami, Himanshu; Anand, Viswanathan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: There is a high prevalence of snoring in paediatric age group. There are various reasons for snoring in children, the most common being adenotonsillar hypertrophy. In our study we intended to establish a relationship between craniomorphological features and snoring. Methods: The sudy objective was to determine the differences in craniofacial cephalometric variables between snoring and non-snoring children. 50 snoring and 50 non-snoring children between the ages of 6 and 12 years were selected. Non-snoring subjects were matched to snoring subjects by age, sex, and ethnicity. Children with adenotonsillar hypertrophy were excluded. Snoring was assessed using a sleep behavior questionnaire administered to parents or guardians. The cephalometric radiographs of the study subjects were traced by a single investigator, 9 measurements of hard and soft tissues were recorded. The paired Student’s t test was used to analyze the cephalometric data. Results: Snoring children manifest a significantly narrower anterior-posterior dimension of the pharynx at the superior and most narrow widths. Snoring children also had a greater length from the hyoid to the mandibular plane. Conclusions: Snoring children appear to present craniofacial factors that differ from those of non-snoring children.